Dynamics in European exports in times of crisis: The impact on growth at home and abroad - Janez Kren; Terence Huw Edwards; Jan Van Hove (Romanian Journal of Fiscal Policy (RJFP), 2015)
While the financial crisis of 2008-2009 led to the great collapse of international trade, the European debt crisis in 2010-2013 did not have such a drastic impact on trade. The collapse has been studied a lot in recent empirical literature, but the European debt crisis has not been investigated thoroughly yet. This paper looks into the impact of economic growth in European exporters and in their export destination markets on export performance as reflected in total export growth and growth in various export margins. Our findings point to an important role for both demand and supply side factors.
Keywords: F14; 330; trade collapse; trade structure; European trade; economic crisis